2022
DOI: 10.1021/acs.jafc.1c05747
|View full text |Cite
|
Sign up to set email alerts
|

Bowman-Birk Major Type Trypsin Inhibitor Derived from Foxtail Millet Bran Attenuate Atherosclerosis via Remodeling Gut Microbiota in ApoE–/– Mice

Abstract: Foxtail millet proteins and their hydrolysates have the potential to prevent atherosclerosis (AS). In our present study, a novel Bowman-Birk type major trypsin inhibitor from foxtail millet bran (FMB-BBTI) with an anti-AS effect was obtained by in vitro gastrointestinal bionic digestion. Further, the anti-AS activity of FMB-BBTI was verified by the classic apoE−/− mice model, characterized by the decreases of the inflammatory cytokines (TNF-α and IL-1β) and atherosclerotic plaque. Importantly, FMB-BBTI remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Our previous research demonstrated that the abundance of intestinal Lactobacillus was significantly increased in the cecal of mice treated by the Bowman−Birktype major trypsin inhibitor from the foxtail millet bran (FMB-BBTI). 22 In the present study, a new strain of Lactobacillus isolated from the cecal treated by FMB-BBTI was identified as L. reuteri SY523. Further, the anti-obesity effect of L. reuteri SY523 was evaluated by the high-fat diet (HFD)-induced obese (DIO) mice model.…”
Section: ■ Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our previous research demonstrated that the abundance of intestinal Lactobacillus was significantly increased in the cecal of mice treated by the Bowman−Birktype major trypsin inhibitor from the foxtail millet bran (FMB-BBTI). 22 In the present study, a new strain of Lactobacillus isolated from the cecal treated by FMB-BBTI was identified as L. reuteri SY523. Further, the anti-obesity effect of L. reuteri SY523 was evaluated by the high-fat diet (HFD)-induced obese (DIO) mice model.…”
Section: ■ Introductionmentioning
confidence: 65%
“…Our previous study found that FMB-BBTI could notably elevate the abundance of intestinal Lactobacillus to alleviate the atherosclerosis effect of apoE –/– mice . It is known that Lactobacillus as an intestinal probiotic plays an important role in metabolic diseases .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bionic digestion of millet bran protein in vitro was followed according to our previously described method. 17 Briefly, millet bran protein extract was digested using the pepsin buffer of 250 units/mL (pH 1.6) at 37 °C for 0.5 h away from light, followed by simulated intestinal digestion using the trypsin buffer of 200 units/mL at pH 6.8 (containing 5% NaHCO 3 ) and 37 °C for 1.5 h away from light. Then, the hydrolysate was incubated for 10 min at 80 °C to stop the digestion, followed by centrifugation for 10 min (at 10000g and 4 °C).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Studies have shown that millet bran protein is the least allergenic protein of the grains known and is suitable for dietary supplement of sub-healthy people. 16 Recent studies have discovered that millet bran contains a series of active proteins and peptides with medicinal values, which exhibit multiple efficacies, such as remodeling gut microbiota, antiatherosclerosis, 17 and antitumor. 18 In the present study, we found that millet bran protein hydrolysate (MBPH) prepared by in vitro gastrointestinal bionic digestion exhibited the potential of anti-NAFLD activity in vitro and in vivo.…”
Section: ■ Introductionmentioning
confidence: 99%